Prevalence and factors associated with hyperphosphatemia in continuous ambulatory peritoneal dialysis patients: A cross-sectional study - Yin, Xiaojing; Zhang, Fan; Shi, Yan (Frontiers in Medicine, 2023)
Background Hyperphosphatemia remains a major complication in patients with Continuous ambulatory peritoneal dialysis (CAPD) leading to increased morbidity and mortality. However, phosphorus management still has many challenges. Objective This study aimed to investigate the prevalence and factors of hyperphosphatemia among continuous ambulatory peritoneal dialysis patients in a tertiary public hospital in Shanghai, China. Methods The single-center cross-sectional study recruited end-stage renal failure patients who received continuous ambulatory peritoneal dialysis (CAPD) for at least 3 months. The participants aged 18–80 years had undergone CAPD between 1 July 2021 and 30 May 2022, in Shanghai, China. The patients’ sociodemographic, clinical, and laboratory data were collected prospectively from medical records and via face-to-face interviews. A sample size of convenience decides the sample size. This study used the information-motivation-behavioral (IMB) skills model as a theoretical framework. The questionnaire included knowledge and behavior of diet and medication in patients with hyperphosphatemia of chronic kidney disease, self-efficacy for managing chronic disease, and social support rating scale. Univariate analysis and binary logistic regression were performed to identify the influencing factors of hyperphosphatemia by SPPS 27.0. Results In total, 141 CAPD patients (73% hyperphosphatemia) were included in the final analysis. In logistic regression analysis, dialysis vintage (OR: 0.975, 95%CI: 0.957–0.993), dialysis exchanges (OR: 0.317, 95%CI: 0.131–0.768), urine output (OR: 0.997, 95%CI: 0.995–0.999), serum albumin (OR: 1.166, 95%CI:1.008–1.349), serum creatinine (OR: 1.005, 95%CI: 1.001–1.008), hyperphosphatemia knowledge behavior score (OR: 0.888, 95%CI: 0.797–0.991), and social support level (OR: 0.841, 95%CI:0.765–0.925) were the influencing factors of hyperphosphatemia. Conclusion Hyperphosphatemia is a frequent complication in CAPD patients. Dialysis vintage, dialysis exchanges, urine output, serum albumin, serum creatinine, hyperphosphatemia knowledge behavior, and social support were the associated factors of hyperphosphatemia in CAPD patients. It is crucial for healthcare providers to maintain phosphorus balance among CAPD patients using phosphorus management strategies.